Simulation technology use in disaster medicine education and training: a scoping review - García Ulerio, José; Al Khatib, Mouhanad; Aammar, Bassma; Ragazzoni, Luca; Barone-Adesi, Francesco; Caviglia, Marta (Frontiers in Disaster and Emergency Medicine, 2025)
BackgroundDisaster medicine (DM) education has increasingly turned to simulation technologies to address the limitations of traditional training methods. Tools such as virtual reality, mobile applications, and e-learning platforms offer immersive and repeatable learning environments. However, the rapid growth of these tools has outpaced efforts to synthesize how they are being applied, what learning goals they target, and how outcomes are reported.ObjectiveThis scoping review aimed to map the current evidence on how simulation technologies are used in DM education and training, with a focus on the educational objectives addressed and the types of tools and metrics reported.MethodsFollowing the PRISMA-ScR guidelines, a comprehensive search of four databases (PubMed, Scopus, Web of Science, and IEEE Xplore) identified original studies published between 2000 and 2024. Thirty-two studies met the inclusion criteria. Data were charted on the type of technology, training topic, learning group, and evaluation methods.ResultsMass casualty triage was the most frequently addressed topic. Virtual reality, mobile application, and serious games were the most common modalities. Most studies reported improvements in knowledge, triage accuracy, or learner confidence. However, evaluation strategies varied widely, with most relying on short-term knowledge tests or self-reported confidence. Few studies addressed the realism of the training environments or the integration of digital tools into broader instructions frameworks.ConclusionTechnology-enhanced DM education shows promise, particularly for immersive triage training. However, inconsistent evaluation practices and limited curricular integration highlight the need for more rigorous, outcome-aligned research to support effective use of simulation technology in this field.